2020
DOI: 10.1111/sum.12652
|View full text |Cite
|
Sign up to set email alerts
|

Effect of timing of cattle urine deposition and pasture composition on nitrogen leaching losses

Abstract: A lysimeter experiment using undisturbed monoliths from a stony silt loam soil was carried out to quantify the effects different pasture types on N losses from urine applied to soil on different dates. Three pasture types were tested: (a) perennial ryegrass (Lolium perenne)/white clover (Trifolium repens) (PRG/WC), (b) perennial ryegrass/white clover/plantain (Plantago lanceolata) (PRG/WC/P) and (c) Italian ryegrass (Lolium multiforum)/white clover/plantain (IRG/WC/P), with four different urine applications da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…A free‐draining soil may allow rapid leaching and so a shorter residence time of N in the root zone could reduce the potential for root exudates to alter N transformations. Talbot et al (2021) suggests that the smaller reduction in N leaching observed in their lysimeter study may be due to the shallow stony soil used compared with the deep silt loam and fine sandy loam soils used by Welten et al (2019) and Carlton et al (2019), respectively.…”
Section: Soil N Processingmentioning
confidence: 90%
See 1 more Smart Citation
“…A free‐draining soil may allow rapid leaching and so a shorter residence time of N in the root zone could reduce the potential for root exudates to alter N transformations. Talbot et al (2021) suggests that the smaller reduction in N leaching observed in their lysimeter study may be due to the shallow stony soil used compared with the deep silt loam and fine sandy loam soils used by Welten et al (2019) and Carlton et al (2019), respectively.…”
Section: Soil N Processingmentioning
confidence: 90%
“…In similar work, Welten et al (2019) observed reductions in N leaching of 15% when urine collected from dairy cows grazing a PR‐WC pasture was deposited on lysimeters containing PL monoculture in summer (relative to ryegrass); this increased to 50% when the urine was deposited in winter. Talbot et al (2021) also examined the timing of urine deposition (from cows grazing PR‐WC) on lysimeters with swards containing 25%–35% PL and found reductions in N leached of 14%–24% compared with lysimeters under PR‐WC, irrespective of timing.…”
Section: Soil N Processingmentioning
confidence: 99%